2015
DOI: 10.1002/etc.2815
|View full text |Cite
|
Sign up to set email alerts
|

Differential uptake and translocation of β‐HCH and dieldrin by several plant species from hydroponic medium

Abstract: To compare the uptake and translocation of hydrophobic organic chemicals (HOCs) by plant species, we performed uptake experiments with β-1,2,3,4,5,6-hexachlorocyclohexane (β-HCH) and 1,2,3,4,10,4,4a,5,6,7,8,8-dimethanonaphthalene (dieldrin) using 5 species: Hordeum vulgare, Glycine max, Solanum lycopersicum, Brassica oleracea, and Cucurbita pepo. We evaluated uptake ability by root concentration factor (RCF) and translocation ability by transpiration stream concentration factor (TSCF). RCFs of β-HCH and dieldr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The RCF (water) data of 37 chemicals with a number of plants/crops from 11 hydroponic studies (Briggs et al, 1982; De Carvalho et al, 2007; Gao et al, 2008; García-Valcárcel et al, 2016; Hinman and Klaine, 1992; Namiki et al, 2015; Romeh, 2014; San Miguel et al, 2013; Su and Zhu, 2006; Su et al, 2009; Xia and Ma, 2006) are listed in Table S1 (Supporting Information). Total data points are 48.…”
Section: Sources Of Literature Datamentioning
confidence: 99%
“…The RCF (water) data of 37 chemicals with a number of plants/crops from 11 hydroponic studies (Briggs et al, 1982; De Carvalho et al, 2007; Gao et al, 2008; García-Valcárcel et al, 2016; Hinman and Klaine, 1992; Namiki et al, 2015; Romeh, 2014; San Miguel et al, 2013; Su and Zhu, 2006; Su et al, 2009; Xia and Ma, 2006) are listed in Table S1 (Supporting Information). Total data points are 48.…”
Section: Sources Of Literature Datamentioning
confidence: 99%
“…Cucurbitaceae have a specific transport mechanism for highly hydrophobic organic chemicals such as dieldrin; it was previously suggested that they have transport proteins that play an important role in root-shoot translocation of dieldrin. 22,23) 2. Bioconcentration factors of organic chemicals in roots and shoots In the preceding section, we discussed differences in the uptake and translocation of organic chemicals among plant species.…”
Section: Uptake and Translocation Of Organic Chemicals In 16 Plant Spmentioning
confidence: 99%
“…It was reported that the RCFs of β-HCH and dieldrin were not changed by dark treatment. 21) Because tolclofos-methyl has similarly high hydrophobicity to β-HCH and dieldrin, it was thought that its uptake ability would not be affected by day length.…”
Section: Effects Of Growth Conditions On Pesticide Uptake By Rootsmentioning
confidence: 99%